Pyridoxine Responsiveness and PNPO Gene Mutations - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators at University Hospital, Zurich, Switzerland, and multiple centers in Europe and Canada, sequenced the pyridoxal 5-phosphate oxidase (PNPO) gene in 31 patients with pyridoxine-responsive seizures but normal biomarkers for antiquitin deficiency and normal sequencing of the ALDH7A1 gene.